Psychological stress and its relationship to behavioral deviation in light of the Corona pandemic from the point of view of workers in government hospitals in Jordan - Al-Rawashdeh, Reem Mahmoud (Journal of Educational and Psychological Sciences, 2022)
The aim of the research is to reveal the relationship between psychological stress and behavioral deviation in light of the Corona pandemic from the point of view of workers in government hospitals in Jordan. To achieve the objectives of the research and data collection, a questionnaire was used as a data collection tool, and the descriptive analytical correlative approach was used, and the study sample consisted of (294) male and female workers in government hospitals in Jordan. The results of the research showed that the level of psychological stress in light of the Corona pandemic from the point of view of workers in government hospitals in Jordan was average, and that the level of behavioral deviation from the point of view of workers in government hospitals in Jordan was also moderate, and the results also showed a positive correlation with statistical significance. Between psychological stress and behavioral deviation in light of the Corona pandemic from the point of view of workers in government hospitals in Jordan. And there were no differences in the perceptions of the study sample members towards the relationship of psychological stress in behavioral deviation due to demographic variables (sex, experience, and place of residence). Based on these results, the researcher recommended the need for state agencies to study the precautionary measures they take due to the Corona pandemic before applying them, knowing their impact on members of society, relieving psychological pressures on them, and constantly evaluating those measures.